Factors Influencing Schoolchildren's Responses to a Questionnaire in Wildlife Conservation Education - Ballouard, Jean-Marie; Mullin, Stephen J.; Ajtic, Rastko; Brito, José Carlos; ElMouden, El Hassan; Erdogan, Mehmet; Feriche, Monica; Pleguezuelos, Juan M.; Prokop, Pavol; Sánchez, Aida; Santos, Xavier; Slimani, Tahar; et al. (International Journal of Science Education, 2015)
Questionnaires are important tools for assessing attitudes regarding conservation issues. However, they are not easily comparable and their reliability has been insufficiently assessed. We examined factors influencing responses to open- and closed-ended questions about animal conservation to more than 600 schoolchildren (9 years old on average). We analysed the level of understanding, controllable (e.g. sample size) and less controllable factors (e.g. affectivity). Most children responded appropriately to the questions, but subtle changes in the phrasing influenced the answers. Affectivity towards endearing species and spontaneity also influenced the responses whereas small sample sizes (∼50 children) provided relatively stable patterns. Overall, we suggest that standardization of questionnaires administered over large spatial and time scales is needed to accurately assess children's attitudes towards conservation issues.
Publisher: Routledge _eprint: https://doi.org/10.1080/09500693.2014.993000
Keywords: Affectivity; Environmental education; Iconic species; Sample size; Survey methodology